Evaluation of official procedures for suicide prevention in hospital from a forensic psychiatric and a risk management perspective. (1st September 2020) - Ferracuti, Stefano; Barchielli, Benedetta; Napoli, Christian; Fineschi, Vittorio; Mandarelli, Gabriele
Abstract: Background: Suicide is a severe public health problem, in 2008 the Italian ministerial recommendation n° 4 on the management of suicide defined key areas for the identification of suicidal risk in hospital wards. The guidelines are important in defining professional liability issues, in line with Law 24 of 8/3/2017 'Gelli-Bianco'. Our study aimed to investigate the appropriateness of the official documents on suicide prevention delivered by Italian hospitals and their compliance with the ministerial recommendation. Methods: The Italian hospitals' public procedures on suicide prevention issued between 2008 and 2019 ( n = 33) were retrieved thorough web search and further evaluated according to their compliance with the 2008 Italian ministerial recommendations. Results: The guidelines documents were generally in line with the ministerial recommendation. However, we found a lack of implementation in the specific training of health professionals. Most guidelines provided no risk stratification, nor specific procedures for different risk degrees or diagnoses. More than half of the documents did not report standardised tools for the assessment of suicidal risk. Conclusions: The public procedures on suicide prevention in Italian hospitals present general indications, leaving room for interpretation. Public procedures should be implemented with greater attention to the elements of judgement in the assessment of suicidal risk. KEY POINTS: Procedures for suicide prevention are of uttermost importance for psychiatrist working in hospital. Standards in suicide risk evaluations are needed. Comparison between procedures can improve risk assessment and evaluation